Neuroinflammation Associated With Inborn Errors of Immunity - Lindahl, Hannes; Bryceson, Yenan T. (Frontiers in Immunology, 2022)
The advent of high-throughput sequencing has facilitated genotype-phenotype correlations in congenital diseases. This has provided molecular diagnosis and benefited patient management but has also revealed substantial phenotypic heterogeneity. Although distinct neuroinflammatory diseases are scarce among the several thousands of established congenital diseases, elements of neuroinflammation are increasingly recognized in a substantial proportion of inborn errors of immunity, where it may even dominate the clinical picture at initial presentation. Although each disease entity is rare, they collectively can constitute a significant proportion of neuropediatric patients in tertiary care and may occasionally also explain adult neurology patients. We focus this review on the signs and symptoms of neuroinflammation that have been reported in association with established pathogenic variants in immune genes and suggest a subdivision based on proposed underlying mechanisms. We delineate emerging pathogenic themes underlying neuroinflammation in monogenic diseases and describe the breadth of the clinical spectrum to support decisions to screen for a genetic diagnosis and encourage further research on a neglected phenomenon.